ANALISIS PENGARUH PMDN, PMA, DAN PDRB TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN PATI TAHUN 1982-2011 - Ifan Restu Bagus Pamungkas (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2013)
Pendapatan Asli Daerah (PAD) masih menjadi parameter untuk mengukur keberhasilan dari pelaksanaan otonomi daerah, salah satu upaya meningkatkan penerimaan daerah adalah menciptakan iklim investasi daerah yang kondusif, agar terjadi proses kegiatan ekonomi yang menjadi tolak ukur dalam pembangunan ekonomi di Kabupaten Pati. Penelitian ini menggunakan data skunder dari Badan Pusat Statistik, Dinas Pendapatan Pengelolaan Kekayaan Aset Daerah, dan Badan Koordinasi Penanaman Modal Daerah Kabupaten Pati dengan periode pengamatan dari tahun 1982-2011. Penelitian ini menggunakan alat analisis regresi berganda dengan model double log, bentuk persamaan regresi Ordinary Least Squares (OLS). Hasil penelitian menunjukkan (1) variabel penanaman modal dalam negeri berpengaruh positif dan signifikan terhadap pendapatan asli daerah di Kabupaten Pati. (2) variabel penanaman modal asing berpengaruh positif dan tidak signifikan terhadap pendapatan asli daerah di Kabupaten Pati. (3) variabel produk domestik regional bruto berpengaruh positif dan signifikan terhadap pendapatan asli daerah di Kabupaten Pati. (4) variabel penanaman modal dalam negeri, penanaman modal asing, dan produk domestik regional bruto secara bersama-sama berpengaruh positif dan signifikan terhadap pendapatan asli daerah di Kabupaten Pati. The original area of revenue (PAD) still be parameters to measure the success of the implementation of regional autonomy, one of the efforts to improve the reception area is to create a conducive investment climate areas, in order to process the economic activities which became a benchmark in economic development. This research using secondary data from the Central Bureau of statistics, the Department of Revenue wealth management Assets, and the investment Coordinating Board of Pati Regency with the observation period from 1982 until the year 2011. This study uses multiple regression analysis tool with double log model, a form of regression equations of Ordinary Least Squares (OLS). The results showed (1) the domestic capital investment variables affect positively and significantly to the original income areas in Pati. (2) the variable foreign investment influential positive and insignificant to the original income areas in Pati. (3) the variable gross regional domestic product of positive and significant effect to the original income areas in Pati. (4) variable domestic capital investment, foreign investment, gross regional domestic product and collectively influence positively and significantly to the original income areas in Pati. The original area of revenue (PAD) still be parameters to measure the success of the implementation of regional autonomy, one of the efforts to improve the reception area is to create a conducive investment climate areas, in order to process the economic activities which became a benchmark in economic development. This research using secondary data from the Central Bureau of statistics, the Department of Revenue wealth management Assets, and the investment Coordinating Board of Pati Regency with the observation period from 1982 until the year 2011. This study uses multiple regression analysis tool with double log model, a form of regression equations of Ordinary Least Squares (OLS). The results showed (1) the domestic capital investment variables affect positively and significantly to the original income areas in Pati. (2) the variable foreign investment influential positive and insignificant to the original income areas in Pati. (3) the variable gross regional domestic product of positive and significant effect to the original income areas in Pati. (4) variable domestic capital investment, foreign investment, gross regional domestic product and collectively influence positively and significantly to the original income areas in Pati.